Assessing the Likelihood of Procedural Intubation During Percutaneous Coronary Intervention - Megan Herson; Sean Tan; Joseph O'Brien; Zhi Hao Teoh; Gavin P. R. Manmathan; Diem Dinh; Angela Brennan; Adam J. Brown; Derek P. Chew (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Preprocedural fasting is widely used before percutaneous coronary intervention (PCI). However, the incidence of procedural intubation during PCI is unknown. This study aims to identify the incidence and predictors for procedural intubation during PCI. Methods and Results A retrospective cohort study was performed on patients undergoing PCI between 2014 and 2021 within the Victorian Cardiac Outcomes Registry. Patients were classified into urgent, semiurgent, or elective PCI on the basis of recorded PCI indication. Those undergoing semiurgent or elective PCI were presumed to be fasted preprocedurally. The incidence of procedural intubation was reported for each PCI group. Inverse probability treatment weighting was used to determine the association between 30‐day death and procedural intubation. Logistic regression was performed to determine clinical, procedural, and lesion characteristics associated with procedural intubation among fasted patients. Among 83 929 patients, the incidence of procedural intubation was 0.5%. Patients undergoing urgent PCI (odds ratio [OR], 19.68 [95% CI, 13.91–27.86]; P<0.01) had the highest risk of procedural intubation. Procedural intubation was associated with increased 30‐day death (OR, 4.79 [95% CI, 3.29–6.96]; P<0.01). Among fasted patients, estimated glomerular filtration rate (OR, 0.99 [95% CI, 0.98–0.99]; P<0.01), cardiogenic shock (OR, 96.24 [95% CI, 56.01–165.35]; P<0.01), out‐of‐hospital cardiac arrest (OR, 3.42 [95% CI, 1.30–8.97]; P=0.01), femoral access (OR, 2.09 [95% CI, 1.38–3.19]; P<0.01), left main disease (OR, 5.77 [95% CI, 3.16–10.54]; P<0.01), type C lesions (OR, 3.86 [95% CI, 1.19–12.56]; P=0.03), and rotational atherectomy (OR, 2.20 [95% CI, 1.03–4.69]; P=0.04) were associated with procedural intubation. Conclusions Despite an association with a worse 30‐day mortality rate, the incidence of procedural intubation during PCI was low. Universal preprocedural fasting may be unnecessary and could be targeted at higher‐risk groups.